The Effect Of Different Constant Temperatures On Some Biological Aspects Of Cowpea Callosobruchus maculatus (F.) (Coleoptera : Bruchidae) - Moanas, Abdulla Hossain (Al-Qadisiyah Journal of Pure Science, 2017)
The effect of the different temperature degrees 15 , 25 , 35 CÂº 0n the biology of cowpea beetle has been studied . The rate male longevity has reached 10.2 days at 15CÂº and this rate is the significantly highest in comparison with other male’s 7.1 and 6.3 days at 25 and 35 CÂº respectively. The male longevities have been compared with the females and the result is that the males have short longevity than females at all the tested temperatures. The rate of females longevities at 35 CÂº has reached 7.2 days with higher significantly difference than their longevities at 15 CÂº and25 CÂº that has reached 9.6 and 11.2 days respectively. The number of eggs per female is highly correlated with the previous selected increasing temperature degrees .The number of eggs per female are 77.5 , 112.8 and 115.7 at 15, 25, 35 CÂº respectively , where as the developmental period decreased significantly with the increase of the temperatures, and the averages are 50.8 , 34.16, 21.3 days at 15 , 25 and 35 CÂº respectively. This study has showed that opposite correlation between daily percentage of progeny and femaleÍƒÍƒÍƒÍƒs age, since this insect gets the highest percentage at first day of oviposition in comparison with other days at all tested temperatures â„…90.6 â„…83 and â„…90.8 at 15 , 25,and 35 CÂº respectively. The intrinsic rate of increase was raising with increase of tested temperatures, the time required to double the population was inversely proportional to the increase of temperatures, that reached 10.9 days , at 15 CÂº and decreased significantly to 6.5 ,4.6 days at 25 and 35CÂº respectively.